What have we learned from the citation classics in Energy and Fuels: A mixed study - Konur, Özcan (SILA SCIENCE, 2012)
The present study explores the content of 50 citation classics in Energy and Fuels published between 1945 and 2011 based on the Arts & Humanities Citation Index (A&HCI), Science Citation Index Expanded (SCIE), and Social Sciences Citation Index (SSCI) and its implications using the scientometric techniques, complementing a scientometric study of the global Energy and Fuels research as well as a scientometric study of 100 citation classics in Energy and Fuels. It was found that 50 citations classics included 9 papers on biofuels, 12 papers on combustion, 10 papers on energy storage and fuel cells, 8 papers on petroleum, 8 papers on solar cells, and 3 papers on waste treatment. These seminal papers provided a context for the stimulation of the future research in these dynamic areas with a focus on environment-friendly biofuels, fuel cells, and solar cells as a viable alternative for the fossil-based fuels for the key stakeholders. The scientometric analysis has a great potential to gain valuable insights into the evolution of the citation classics in Energy and Fuels, complementing the scientometric studies in the fields of the renewable energies as well as other dynamic research fields providing a unique insight on the incentive structures for all the key stakeholders in the field.
Keywords: Citation classics; Energy; Fuels; Literature review; Research evaluation; Research productivity; Scientometrics; Web of Knowledge